Efektifitas Pemberian Diet Beras Merah Dalam Menurunkan Kadar Gula Darah Pada Penderita Diabetes Mellitus Di Puskesmas Pademawu Pamekasan - Kuszairi, Kuszairi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
Diabetes mellitus (DM) is a disease in which blood glucose levels are high because the body can not release or use insulins sufficiently. Treatment of diabetes includes weight control, exercise and diet. One way of diet is to use brown rice. The purpose of this study to determine the effectiveness of red rice diet in lowering blood sugar levels in patients with DM. The design of this research used Quasy-Experiment research design with Simple Random Sampling method. The sample used was 16 respondents from population of 76 DM patients who performed outpatient at Puskesmas Palengaan in June 2008. Data collection was done by observing the blood sugar level before and after intervention of red rice diet using GlucoDr tool. After being tabulated, the existing data were analyzed by using Paired Sample T Test with a significance level of 0.05. The results of statistical tests obtained that H0 rejected and H1 accepted, meaning red rice diet is effective against the decrease in blood sugar levels DM patients with a value of t count of 7.202 with a significant level of 0.000. Given the results of this study proves that the red rice diet can reduce blood sugar levels of DM patients so the need for awareness of DM patients to implement a red rice diet in order to reduce the risk of complications from DM.Â